Blind Race in support of the Filatov Institute of Eye Disease and Tissue Therapy (Ukrainian Journal of Ophthalmology, 2025)
The 27th Charity Chestnut Run took place on Independence Square in Kyiv on May 26 (The Day of Kyiv), 2019. The Chestnut Run is the largest charitable sports event in Ukraine. This year there were 600 teams on Maidan, and the total number of people taking part in the race was more than 20,000.In addition, this year, for the first time in the Run’s history, the Run included a new race, the Blind Race in support of the Filatov Institute of Eye Disease and Tissue Therapy of the city of Odesa. The participants ran in pairs, one guiding, one blindfolded. In this way, they tried to experience the feelings of blind people for a few minutes at least, and to get the idea of being blind, whereas the organizers of the event tried to attract public attention to the Childhood Blindness Prevention Center to be established at the Filatov Institute.